2012
DOI: 10.2298/hel1256089h
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of resistance of new sunflower hybrids to broomrape in the breeding programs in Novi Sad

Abstract: Broomrape (Orobanche cumana Wallr.) presents a serious problem in sunflower production in a number of countries, it reduces sunflower seed yield and negatively affects other sunflower traits in sunflower production. Continued work on creating new sunflower hybrids resistant to broomrape requires testing of breeding materials in both field conditions and controlled conditions of a greenhouse. The best solution is to do the testing simultaneously in order to verify the congruence of the evaluation of the broomra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In order to discover new resistance genes to Orobanche, both CWR per se (Terzić et al, 2010;Jocković et al, 2018) and inbred lines of cultivated sunflower originating from interspecific crosses have been tested. As a result, resistance genes to new races of O. cumana were recently detected in inbred lines originating from crosses with H. deserticola (Hladni et al, 2012), H. tuberosus and H. divaricatus (Cvejić et al, 2014). The resistance genes from these sources have been subsequently mapped, and the developed molecular markers will expedite their transfer into commercial lines (Imerovski et al, 2013(Imerovski et al, , 2016(Imerovski et al, , 2019.…”
Section: Use Of Cultivated Sunflower and Cwr Resources In Breedingmentioning
confidence: 99%
“…In order to discover new resistance genes to Orobanche, both CWR per se (Terzić et al, 2010;Jocković et al, 2018) and inbred lines of cultivated sunflower originating from interspecific crosses have been tested. As a result, resistance genes to new races of O. cumana were recently detected in inbred lines originating from crosses with H. deserticola (Hladni et al, 2012), H. tuberosus and H. divaricatus (Cvejić et al, 2014). The resistance genes from these sources have been subsequently mapped, and the developed molecular markers will expedite their transfer into commercial lines (Imerovski et al, 2013(Imerovski et al, , 2016(Imerovski et al, , 2019.…”
Section: Use Of Cultivated Sunflower and Cwr Resources In Breedingmentioning
confidence: 99%
“…Many genetic studies on the sunflower resistance carried out in many countries indicated that sunflower resistant to broomrape is controlled by either a single dominant gene (Burlov and Kostyuk, 1976; Pogorletsky and Geshele, 1976;Ish-Shalom-Gordon et al, 1993) or multiple genes. Velasco et al (2012) also confirmed that dominant alleles in sunflower controlled the resistance against race G. However, some results indicated that the sunflower resistance to broomrape was controlled by multiple genes, for example two recessive genes or6 and or7 control resistance to race F (Cubero, 1991;Pérez-Vich et al, 2004;Hladni et al, 2012;Louarn et al, 2016). In China, Zhang et al generated three combinations using a resistant line P1 and a susceptible line P2, and identified the resistance and susceptible separation ratio in F1, F2 and BC1 population (P2), they concluded that sunflower resistance to broomrape was controlled by a pair of dominant alleles; hence proposed a breeding procedure to improve the resistance level of new varieties (Zhang et al, 2006).…”
Section: Resistance Breedingmentioning
confidence: 85%